Inclusive leadership and work-family enrichment: the roles of relational energy and power distance - Zhang, Junlin; Liu, Zongrui; Wang, Jianli (Frontiers in Psychology, 2025)
Few studies have systematically examined how inclusive leadership affects employee work-family enrichment. Based on social contagion theory and the resource model of work-family enrichment, this research examined how and when inclusive leadership influences employees’ relational energy and subsequent work-family enrichment. Additionally, we examined whether power distance might influence the positive effect of inclusive leadership on relational energy. The results from a cross-sectional survey of 673 Chinese participants in Study 1 showed that inclusive leadership is positively related to work-family enrichment, and relational energy mediates the relationship between inclusive leadership and work-family enrichment. We also found that the positive effect of inclusive leadership on relational energy was greater under lower levels of power distance, as was the indirect effect of inclusive leadership on work-family enrichment via relational energy. Study 2, using three-wave data collected from 241 Chinese employees, verified the results that relational energy mediates the relationship between inclusive leadership and work-family enrichment.